Polymorphic regulation of mitochondrial fission and fusion modifies phenotypes of microglia in neuroinflammation - Mitsuhiko Katoh (Nature Portfolio, 2017)
Abstract Microglia are the resident macrophages of the central nervous system and play complex roles in the milieu of diseases including the primary diseases of myelin. Although mitochondria are critical for cellular functions and survival in the nervous system, alterations in and the roles of mitochondrial dynamics and associated signaling in microglia are still poorly understood. In the present study, by combining immunohistochemistry and 3D ultrastructural analyses, we show that mitochondrial fission/fusion in reactive microglia is differentially regulated from that in monocyte-derived macrophages and the ramified microglia of normal white matter in myelin disease models. Mouse cerebral microglia in vitro demonstrated that stimulation of TLR4 with lipopolysaccharide, widely used to examine microglial reactions, caused the activation of the mitochondrial fission protein, dynamin-related protein 1 (Drp1) and enhanced production of reactive oxygen species (ROS). The increase in the ROS level activated 5′ adenosine monophosphate-activated protein kinase (AMPK), and facilitated elongation of mitochondria along the microtubule tracks. These results suggest that the polymorphic regulation of mitochondrial fission and fusion in reactive microglia is mediated by distinct signaling under inflammatory conditions, and modulates microglial phenotypes through the production of ROS.